Mutational Landscape of Bone Marrow CD19 and CD138 Cells in Waldenström Macroglobulinemia (WM) and IgM Monoclonal Gammopathy of Undetermined Significance (IgM MGUS) - Alessandra Trojani; Alessandro Beghini; Luca Emanuele Bossi; Marta Rachele Stefanucci; Cassandra Palumbo; Antonino Greco; Annamaria Frustaci; Barbara Di Camillo; Roberto Cairoli (Cancer Medicine)
ABSTRACT Background Despite recurrent and activating mutations, including MYD88, CXCR4, ARID1A, KMT2D, and CD79B were identified, the genetic basis for Waldenström's Macroglobulinemia (WM) and the risk of progression of IgM MGUS to WM remain to be fully elucidated. Methods We investigated the mutation status of WM (n = 8), sWM (n = 7), and IgM MGUS (n = 5) patients, by performing high‐throughput targeted AmpliSeq NGS on 117 target genes. Specifically, we analyzed the CD19+ cells from 15 WM/sWM patients and five IgM MGUS patients. We also analyzed the CD138+ cells from four WM/sWM patients and two IgM MGUS patients. Results We detected the classic mutation MYD88L265P in 93% of WM/sWM and in 60% of IgM MGUS patients. The CXCR4S338Ter mutation was identified in 26% of WM/sWM patients, whereas it was undetectable in IgM MGUS subjects. Interestingly, we identified new mutated genes, including WNK2 somatic mutations affecting 46% of WM/sWM patients, for which a recurrent allelic variant (V1635Ter) was observed in this cohort. Moreover, sequencing evaluation revealed recurrently frameshift or missense mutations involving NFKB2 (L473Afs) in 60% of IgM MGUS and 20% of WM/sWM, PTPN13 (P1546Tfs) in 20% of IgM MGUS and 7% of WM/sWM, CARD11 (S622del) in 20% of IgM MGUS and 20% of WM/sWM, KMT2C (I823T) in all IgM MGUS and 93% of WM/sWM, and ATM in 20% of IgM MGUS and 47% of WM/sWM patients. Conclusion In conclusion, we uncovered new insights into the mutational landscape of WM, depicting a more complex involvement of the NF‐kB pathway, and providing evidence of the recurrence of some variants (MYD88, IL17RB, NFKB2, ATM, CARD11, PTPN13, and WNK2) also in IgM MGUS.